Thermodynamic properties of the dodecylbenzenesulfonic acid-acetone binary liquid mixture using a modified flory theory (Chemical Engineering Research Bulletin, 2018)
Prigogine–Flory–Patterson (P-F-P) theory was applied for the correlation the experimental data of excess molar volume for the binary liquid mixture of DBSA-Acetone at the temperature range of (293.15-303.15 K). The three contribution terms (pressure, interaction and free volume) in the P-F-P equation were compared with the total effect of P-F-P equation. A positive excess molar volume were obtained at all the range of mole fraction and at all the temperatures. The maximum value of excess molar volume was positioned at the 0.4 mole fraction. Eyring-Flory-Huggins theory was found useful in the estimation of the viscosity deviation variation with mole fraction at the same temperature range. A negative deviation was found in the viscosity for all the range of temperature and mole fraction. The maximum deviation in the viscosity was found at the mole fraction of 0.4. The increase in the negative deviation values with temperature was interpreted as a result of the decrease in the attractive forces between the like molecules.Chemical Engineering Research Bulletin 20(2018) 30-35